Pedestrian crossing guide based on Android-Cloud platform for blind people - Hasan, Anik; Sharif, Nasrat (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.